Karakteristik Agronomis 10 Galur Tanaman Tomat Hasil Persilanggan Pada Budidaya Organik - Sri Rustianti; Sri Mulatsih; Duni Sahputra; Prihanani (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2026)
This study aimed to evaluate the agronomic performance of ten tomato breeding lines under an organic cultivation system and to identify potential lines for further development. The experiment was conducted from March to July 2025 in Bengkulu, Indonesia, using a Completely Randomized Design (CRD) with ten tomato breeding lines and three replications. The tested lines were G3, G4, G5, G6, G7, G9, G12, G13, G15, and G16. Each experimental unit consisted of three plants, resulting in a total of 90 plants. Organic cultivation practices included the application of goat manure, fermented liquid organic fertilizer, and botanical pesticides derived from garlic extract. Observed variables included vegetative growth, reproductive traits, and yield components. Data were analyzed using analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test (DMRT) at the 5% level when significant differences occurred. The results showed that the tested tomato breeding lines did not differ significantly in plant height, leaf number, branch number, stem diameter, flowering age, harvesting age, flower number, fruit number, fruit weight, and fruit diameter. However, descriptive evaluation indicated that G12 and G15 consistently produced higher flower number, fruit number, and fruit weight than the other lines. These findings suggest that all tested lines exhibited relatively stable adaptation under organic cultivation conditions, while G12 and G15 showed greater potential for further multilocation evaluation and organic tomato breeding programs.